The SAGE handbook of research on teacher education - Clandinin, D. Jean Clandinin; Husu, Jukka (SAGE Publications, 2017)
The SAGE handbook of research on teacher education provides an international overview of the current landscape of teacher education research, as well as the imagined futures. This handbook is a landmark collection for all those interested in current research in teacher education and how research can influence future teacher education practices and policies. The two volumes are divided into sub-sections.